2021
DOI: 10.23887/jet.v5i2.34462
|View full text |Cite
|
Sign up to set email alerts
|

Learning Multimedia Based on RPG Maker MV Material for Circumference and Area of Flat Shapes for Elementary School Students

Abstract: It is known that the implementation of learning during the Covid-19 pandemic causes students to become bored quickly and online learning multimedia is not yet available. To overcome this, development research is carried out to produce designs and learn multimedia that are suitable for use after going through the material expert test, learning media experts test, learning design experts test, individual trials, and small group trials. This research develops circumference and area of flat shapes for fourth-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
2
4
0
3
Order By: Relevance
“…Previous research findings state that multimedia is very effective in learning (Handaru & Pujiriyanto, 2020;Herdiyanto et al, 2020). Other findings also reveal that interactive multimedia can increase student motivation in learning (Ahmadi et al, 2017;Dewi & Sujana, 2021). Based on the results of this study and previous research, valid multimedia is feasible to use in learning activities because it helps students in learning.…”
Section: Discussionsupporting
confidence: 62%
“…Previous research findings state that multimedia is very effective in learning (Handaru & Pujiriyanto, 2020;Herdiyanto et al, 2020). Other findings also reveal that interactive multimedia can increase student motivation in learning (Ahmadi et al, 2017;Dewi & Sujana, 2021). Based on the results of this study and previous research, valid multimedia is feasible to use in learning activities because it helps students in learning.…”
Section: Discussionsupporting
confidence: 62%
“…However, the current problem is the need for more technology-based learning media to facilitate student learning. Previous research findings also revealed teachers' difficulties developing technologybased learning media to support learning (Dewi & Sujana, 2021;Dinayusadewi et al, 2020;Siregar & Kurniati, 2022). Other findings also confirm that the lack of learning media that facilitates students impacts low student learning outcomes (Filivani & Agung, 2021;Pramestika et al, 2020;Yolanda et al, 2022).…”
Section: Introductionsupporting
confidence: 54%
“…RPG is able to facilitate students to understand teaching materials and help student learning problems such as boredom (Rasyid & Gaffar, 2019;Saputri & Ferawati, 2021). They found that RPG educational games can be useful for the learning process such as gaining new knowledge and making the learning process more fun (Dewi & Sujana, 2021;Faiz et al, 2017;Wang et al, 2018) . The RPG learning media developed is also very feasible in terms of functionality and product use.…”
Section: Discussionmentioning
confidence: 99%
“…Digital educational games in the form of Role-Playing Games (RPGs) allow players to play the game from the character's point of view to explore the complex virtual world, and the challenges associated with the story that players have to face (Dewi & Sujana, 2021;Pramuditya et al, 2018;Wang et al, 2018) . Because students will find games interesting, more and more teachers are looking for ways to incorporate educational games into their classrooms in order to attract students' enthusiasm (Anastasiadis et al, 2018;Ge & Ifenthaler, 2018;Prager, 2019).…”
Section: Introductionmentioning
confidence: 99%